A hazai egészségturizmus minőségügyi értékelése - Marosi, Tibor; Molnár, Pál (Jelenkori Társadalmi és Gazdasági Folyamatok, 2011)
In recent years, the role of health tourism has become more significant in Hungary due to growing health awareness, good domestic conditions and the increasingly completed health services. Beside the conditions Hungary has long traditions and internationally accepted references in this area, nowadays wellness tourism is becoming increasingly popularHungary is one of the biggest source of thermal waters, thus health tourism can be a vital part of the domestic tourism industry. The developments of health tourism services are also important for tourist destination. In this paper an overall assessment was done about the services belong to health tourism. Applying a questionnaire survey the evaluation of a Hungarian practice was accomplished, and about 100 wellness hotel were involved, from all parts of Hungary. The results indicate that quality management systems are applied in high rate, but requirements are not determined or applied precisely. Also important establishment is that wellness hotels take the necessary steps to shape up the inner and outer environment perfectly, but feedbacks and direct surveys of guests are missing in many cases. The competition is strong in the market of health tourism, if Hungary means to strengthen his position has pay more attention for implementation of quality practice.